Factors Undermining the Use of Seasonal Climate Forecasts Among Farmers in South Africa and Zimbabwe: Implications for the 1st and 2nd Sustainable Development Goals - Ebhuoma, Eromose E. (Frontiers in Sustainable Food Systems, 2022)
The adverse effects of climate change on food production coupled with growing inconsistencies in Indigenous knowledge systems have necessitated some farmers' willingness to rely on seasonal climate forecasts (SCFs) to make informed farming decisions. SCFs provide information regarding the likelihood that the rainfall in the forthcoming season will be higher, lower or normal. While SCFs have scaled up food production among some rural households in Sub-Saharan Africa (SSA), some farmers find it difficult to plug into this vital technology. Failure to utilize SCFs could have severe consequences for household food and nutrition security, especially in semi-arid countries like South Africa and Zimbabwe. By systematically unpacking the literature in South Africa and Zimbabwe from 2011 to 2021, this article seeks to demystify the factors that hamper the use of SCFs in the aforementioned countries. Results indicate that failure to comprehensively understand and interpret probabilistic forecasts as well as ill-timing of forecast dissemination, among others, are factors that undermine the use of SCFs. These issues are discussed both within the broader theoretical debates revolving around ways to dismantle the barriers undermining the use of SCFs in SSA, which could hamper the attainment of both the first and second sustainable development goals.